Risk management in long-term care : a quick reference guide - Weinberg, Andrew David (Springer Pub. Co., 1998)
"A practical, effective, and thorough risk management tool, this book helps health professionals address common problem areas in order to avoid litigation. Risk topics covered include: injury from physical restraint, resident abuse and neglect, infection control, polypharmacy and medication use, falls and much more." "This volume also features valuable information on ways to respond to legal claims. Each chapter concludes with 10 tips for the reader. The appendices contain case studies with questions for discussion and a useful resource list of organizations." "This handy guide is indispensable to administrators, nurses, and physicians, as well as students of health administration."--BOOK JACKET.